Bacteria tracking in a surgical nursing: experience report (Research, Society and Development, 2020)
Objective: describe the implementation of routine screening for multidrug-resistant germs in a general surgery ward. Methodology: is an experience report based on an educational approach about the screening of multidrug-resistant germs by residents in Clinical Surgical Nursing at a university hospital in Rio de Janeiro. Results: the educational activity was carried out for 4 subsequent days in November 2019, in the General Surgery ward. The target audience was the nursing team composed of nurses and nursing technicians. The application of pre and post-tests was planned, but it was not possible due to the care demand in the sector. Conclusion: the intervention provided improvements to the routine of the infirmary, in addition to contributing to better patient care and knowledge of professionals. However, the evaluation of the activity was hampered by the great demand for labor in the sector.